Unique anisotropic optical properties of a highly stable metal–organic framework based on trinuclear iron(iii) secondary building units linked by tetracarboxylic linkers with an anthracene core. Issue 17 (24th February 2016) - Vinogradov, A. V.; Milichko, V. A.; Zaake-Hertling, H.; Aleksovska, A.; Gruschinski, S.; Schmorl, S.; Kersting, B.; Zolnhofer, E. M.; Sutter, J.; Meyer, K.; Lönnecke, P.; Hey-Hawkins, E.
Abstract : A highly stable metal–organic framework, [{Fe3 (ACTBA)2 }X·6DEF] n (1 ; X = monoanion), is reported. Abstract : A highly stable metal–organic framework, [{Fe3 (ACTBA)2 }X·6DEF] n (1 ; X = monoanion), based on trinuclear iron(iii ) secondary building units connected by tetracarboxylates with an anthracene core, 2, 6, 9, 10-tetrakis( p -carboxylatophenyl)anthracene (ACTBA), is reported. Depending on the direction of light polarisation, crystals of1 exhibit anisotropic optical properties with birefringence Δ n = 0.3 ( λ = 590 nm).